Final theory : a novel - Alpert, Mark (New York : Simon & Schuster, 2008)
David Swift, a professor at Columbia University, is on the run for his life from the FBI and a ruthless mercenary as he frantically tries to work out an unpublished Einstein theory.
"A Touchstone book."
Keywords: Physics teachers -- Fiction; Unified field theories -- Fiction